Sistem Pakar Mendiagnosa Gizi Buruk Pada Balita Menggunakan Teorema Bayes - Ratna Noviani; Sulindawaty Sulindawaty (Jurnal Nasional Komputasi dan Teknologi Informasi (JNKTI), 2020)
The development of information and communication technology is increasingly developing following the development of human civilization to date. Technological developments have also penetrated into the health sector that is able to process and think like humans, namely Artificial Intelligence technology. Artificial intelligence is divided into several fields of science, one of which is expert systems. One system that experts use is to diagnose malnutrition in toddlers. In the Expert System Utilization diagnose malnutrition in toddlers using the appropriate Bayes theorem to be applied to this problem. With this expert system, it can make it easier for the community or Pagar Merbau health center agency to make decisions through alternatives and criteria obtained from information or data managers. The accuracy value for the accuracy of manual calculations and calculations in expert systems to diagnose malnutrition in toddlers using the Bayes theorem has an accuracy of 99%. In this study, there were 5 names of malnutrition in toddlers and 25 names of malnutrition in toddlers.